Cell fusion in health and disease II: cell fusion in disease - Dittmar, Thomas; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
Although cell fusion is an omnipresent process in life, to date considerably less is still known about the mechanisms and the molecules being involved in this biological phenomenon in higher organisms. In Cell Fusion in Health and Disease Vol 1 & Vol 2 leading experts will present up-to-date overviews about cell fusion in physiological and patho-physiological processes, which further covers the current knowledge about cell fusion-mediating molecules. Volume 1 deals with Cell Fusion in Health and will cover aspects of cell fusion in fertilization, placentation, in C. elegans, in skeletal muscle development and tissue repair, and the use of cell fusion for cellular reprogramming and cancer vaccine development. Volume 2 focuses on Cell Fusion in Disease with a particular emphasis on the role of cell fusion in cancer development and progression. Thus, Cell Fusion in Health and Disease Vol 1 & Vol 2 represents a state-of-the-art work for researchers, physicians or professionals being interested in the biological phenomenon of cell fusion and bey
1. Introduction / Thomas Dittmar and Kurt S. Zänker -- 2. Horizontal gene transfers with or without cell fusions in all categories of the living matter / Josph G. Sinkovics -- 3. Class III viral membrane fusion proteins / Marija Backovic and Theodore S. Jardetzky -- 4. Human trophoblast in trisomy 21 : a model for cell-cell fusion dynamic investigation / André Malassiné ... [et al.] -- 5. Cell fusion and hyperactive osteoclastogenesis in multiple myeloma / Franco Sylvestris ... [et al.] -- 6. Cell fusion hypothesis of the cancer stem cell / Xin Lu and Yibin Kang -- 7. Expression of macrophage antigens by tumor cells / Ivan Shabo and Joar Svanvik -- 8. Leukocyte-cancer cell fusion : initiator of the Warburg effect in malignancy? / Rossitza Lazova, Ashok Chakraborty, and John M. Pawelek -- 9. Cell fusion, drug resistance and recurrence CSCs / Christa Nagler, Kurt S. Zänker, and Thomas Dittmar -- 10. The role of micorvesicles in malignancies / Erna
Electronic reproduction.
Keywords: Cell hybridization; Electronic book